Carbon-based nanomaterial intervention and efficient removal of various contaminants from effluents – A review. (January 2023) - Manimegalai, Sengani; Vickram, Sundaram; Deena, Santhana Raj; Rohini, Karunakaran; Thanigaivel, Sundaram; Manikandan, S.; Subbaiya, R.; Karmegam, N.; Kim, Woong; Govarthanan, M.
Abstract: Water treatment is a worldwide issue. This review aims to present current problems and future challenges in water treatments with the existing methodologies. Carbon nanotube production, characterization, and prospective uses have been the subject of considerable and rigorous research around the world. They have a large number of technical uses because of their distinct physical characteristics. Various catalyst materials are used to make carbon nanotubes. This review's primary focus is on integrated and single-treatment technologies for all kinds of drinking water resources, including ground and surface water. Inorganic non-metallic matter, heavy metals, natural organic matter, endocrine-disrupting chemicals, disinfection by-products and microbiological pollutants are among the contaminants that these treatment systems can remediate in polluted drinking water resources. Significant advances in the antibacterial and adsorption capabilities of carbon-based nanomaterials have opened up new options for excluding organic/inorganic and biological contaminants from drinking water in recent years. The advancements in multifunctional nanocomposites synthesis pave the possibility for their use in enhanced wastewater purification system design. The adsorptive and antibacterial characteristics of six main kinds of carbon nanomaterials are single-walled carbon nanotubes, multi-walled carbon nanotubes, graphene, graphene oxide, fullerene and single-walled carbon nanohorns. This review potentially addressed the essential metallic and polymeric nanocomposites, are described and compared. Barriers to use these nanoparticles in long-term water treatment are also discussed. Graphical abstract: Image 1 Highlights: Utilization of CNTs in contaminants removal from waster has been reviewed. Inorganic non-metal, EDCs, disinfection by-products and microbial pollutants require remediation. Visible photoactivity and better charge separation can be achieved by combining TiO2 and CNTs. CNT filters can effectively remove bacteria and viruses through adsorption and killing.